The Features of Drum Language as a Means of Communication in Nigeria - Pinmiloye, Olukunle Joshua (2015)
This study examined musical linguistic components of the drum language elucidated the use of drums in Nigeria's socio-cultural context and identified, the connection between theory and practice in drum language communication. This was with a view to revealing the importance of drum language as a special means of non-verbal communication.